Scottish public sector employment and pay - Magdalena Dominguez; Ben Zaranko (Institute for Fiscal Studies (IFS), 2025)
Hospitals, schools, councils and other parts of the public sector are a major employer in Scotland. The public sector paybill is also a substantial part of government spending. Recent years have seen larger-than-expected increases in both public sector employment and pay, the latter driven by high rates of inflation following the COVID-19 pandemic and Russia's invasion of Ukraine. A rising paybill is particularly challenging in a Scottish context because while the increases in funding it receives from the UK government via the Barnett formula are populationbased, its share of the increase in paybill costs is likely to be higher, due to higher current levels of pay in Scotland compared with the UK as a whole. The same is true of forthcoming increases in employers' National Insurance contributions. This chapter of our Scottish Budget report sets out the facts and figures for Scottish public sector employment and pay, and considers the implications for Scottish Government policy.
Keywords: 330; Employment and income; Government finances and spending; Devolved government finances; Government spending; Labour supply and workforce; Pay; Public sector; Scotland